Perbedaan Keterampilan Berpikir Kreatif Siswa Terhadap Strategi Pembelajaran Multiple Intelligences Dan Contextual Teaching Learning - Rahmatul Bayyinah; Syubhan An'nur; Suriasa Suriasa (Universitas Lambung Mangkurat, 2014)
ABSTRACT: Creative thinking skills of the students of class VII MTsN Mulawarman Banjarmasin on physics lesson is low. This is due to the evaluation of learning rarely apply creative thinking skills, as well as the implementation of learning activities predominantly on one type of intelligence, logical-mathematical. Therefore, we need a strategy that can develop creative thinking skills and refers to the different spheres of intelligence, multiple intelligences learning strategies that contextual teaching and learning (CTL). The general objective of this study is to describe the differences between the multiple intelligences and learning strategies (CTL) to the creative thinking skills of students. Research conducted a quasi-experimental study design randomized pretest and posttest control group. The study population was all students of class VII MTsN Mulawarman Banjarmasin and the sample were students of class VII D as an experimental class and E class VII as a control class. Data collection was conducted using test instruments, and multiple intelligences scale questionnaire. The analysis technique used is descriptive statistics and parametric assumptions to test the hypothesis. The results showed that in general there is a difference between the students' creative thinking skills and classroom control classroom experiment. This is supported by the results of the analysis, which was performed on the data posttest and gain scores, two classes, namely thit , 3.177 > 1.665 ttab , and thit , 2.104 > ttab , 1,665 .multiple intelligences learning strategies; creative thinking skills